2004
DOI: 10.1515/znc-2004-9-1009
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Fractions and Compounds from Calophyllum brasiliense (Clusiaceae/Guttiferae)

Abstract: Calophyllum brasiliense (Clusiaceae/Guttiferae) is a native Brazilian medicinal plant traditionally used against several diseases, including infectious pathologies. Crude methanolic extracts (CME) and two fractions, denoted non-polar (soluble in chloroform) and polar (nonsoluble in chloroform), were prepared from different parts of the plant (roots, stems, leaves, flowers and fruits) and studied. The following compounds were isolated and tested against pathogenic bacteria and yeasts by determination of the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 2 publications
(1 reference statement)
1
30
0
6
Order By: Relevance
“…Pretto and his co-authors showed that all the parts (roots, stems, leaves, flowers and fruits) of C. brasiliense exhibited antimicrobial activity against Gram-positive bacteria and no activity was observed against Gram-negative bacteria and yeasts tested (Pretto et al, 2004). On the other hand, this difference in susceptibility between the bacteria is related to the outer membrane of gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretto and his co-authors showed that all the parts (roots, stems, leaves, flowers and fruits) of C. brasiliense exhibited antimicrobial activity against Gram-positive bacteria and no activity was observed against Gram-negative bacteria and yeasts tested (Pretto et al, 2004). On the other hand, this difference in susceptibility between the bacteria is related to the outer membrane of gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Wide phytochemical studies have been reported that Calophyllum genus rich in xanthones, coumarins, biflavonoids, chalcones, benzofurans and triterpenes (Pretto et al, 2004;Taher et al, 2005). Some of these species are commonly employed in folk medicine, where it is used to treat bronchitis, gastric and hepatic disturbances, pain, inflammation, diabetes, hypertension, diarrhea, herpes, rheumatism, varicose, hemorrhoids and chronic ulcer, also it is used for treating toothache and to prevent wound infections by micro-organisms (Cottiglia et al, 2004;Pretto et al, 2004). As there is no data relative to phytochemical and biological activity of the rubiginosum species had been reported.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus can be inhibited by quercetin, rutin, kaempferol, gallic, coumaric, caffeic, ferulic, neochlorogenic, chlorogenic, protocatechuic and p-hydroxybenzoic acids, a total of 11 different compounds. Among them the most powerful are kaempferol, chlorogenic, neochlorogenic and protocatechuic acids (Pretto et al 2004;Teffo et al 2010;Fiamegos et al 2011). From the tested plants C. monogyna was the plant with the highest number of them, 7, followed by G. purpureum with 6.…”
Section: Antibacterial Propertiesmentioning
confidence: 96%
“…The hexane and ethyl acetate stem bark extracts of Calophyllum brasiliense showed selective activity for gram-positive bacteria Staphylococcus aureus, Staphylococcus epidermidis and Streptococcus agalactiae with MIC values of 1000 µg/mL, but had no action against gramnegative bacteria (MICs >1000 µg/mL). Pretto et al (2004) demonstrated that methanol extract and polar and non-polar fractions from roots, stem, leaves, flowers and fruits from C. brasiliense exhibited selective antimicrobial activity against gram-positive bacteria without effect against gram-negative bacteria. Corttiglia et al (2004) showed that secondary metabolites obtained from hexane and ethyl acetate stem bark extracts from C. brasiliense displayed antimicrobial activity against gram-positive bacteria.…”
Section: Seven Medicinal Plants (Bowdichia Virgilioides Calophyllum mentioning
confidence: 99%